1996
DOI: 10.1007/s004200050125
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and the indoor environment: the significance of emission of formaldehyde and volatile organic compounds from newly painted indoor surfaces

Abstract: As a part of the worldwide European Community Respiratory Health Survey, possible relations between asthma and emissions from newly painted indoor surfaces were studied. The participants (n = 562) answered a self-administered questionnaire, with questions on symptoms and indoor exposures, including indoor painting, during the last 12 months. The participants also underwent a structured interview, spirometry, peak flow measurements at home (PEF), methacholine provocation test for bronchial hyper-responsiveness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
180
4
6

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 301 publications
(198 citation statements)
references
References 34 publications
8
180
4
6
Order By: Relevance
“…They were combined into one dampness mould variable. Finally, there was one question about indoor painting the last 12 months in the home (Wieslander et al, 1997). The statistical models included adjustments for these home environment factors.…”
Section: Assessment Of the Home Environment And Microbial Components mentioning
confidence: 99%
“…They were combined into one dampness mould variable. Finally, there was one question about indoor painting the last 12 months in the home (Wieslander et al, 1997). The statistical models included adjustments for these home environment factors.…”
Section: Assessment Of the Home Environment And Microbial Components mentioning
confidence: 99%
“…Wieslander et al (150) aimed to examine respiratory symptoms and asthma outcomes in relation to indoor paint exposures in the Asthma Occurrence • Epidemiologic evidence for asthma and air toxics Environmental Health Perspectives • VOLUME 110 | SUPPLEMENT 4 | AUGUST 2002 last year. They selected an enriched random sample of 562 adult subjects, including asymptomatic responders along with all reporting asthma or nocturnal dyspnea (216 subjects), using the same survey source population as Norbäck et al (149) in Uppsala.…”
Section: Epidemiologic Evidence For Voc Mixturesmentioning
confidence: 99%
“…In the United States, the prevalence of asthma is approximately 7% among adults and 9% among children (Akinbami et al 2009;Moorman et al 2007). Among adults, some studies have reported a positive association between formaldehyde and asthma (Wieslander et al 1997), while others have not (Krzyzanowski et al 1990). It has been suggested that certain groups, specifically children, may be particularly sensitive to formaldehyde exposure; however, as with adults, the results have been inconsistent, with some studies reporting an association (Garrett et al 1999) and others not (Symington et al 1991).…”
mentioning
confidence: 99%